Pregnancy outcomes in freeze-all versus fresh embryo transfer cycles of women with adenomyosis and endometriosis: a systemic review and meta-analysis - Han, Yixian; Liu, Chang; Liu, Dong; Wu, Lukanxuan; Huang, Wei (Frontiers in Endocrinology, 2025)
BackgroundEndometriosis (EMS) and adenomyosis have adverse effects on women’s fertility. In vitro fertilization (IVF) and intracytoplasmic sperm injection (ICSI) are effective treatments for these diseases. Research has shown that different embryo transfer strategies in IVF/ICSI can influence gestational outcomes. This systematic review and meta-analysis aimed to evaluate the impact of freeze-all embryo transfer (FET) versus fresh embryo transfer (ET) strategies in IVF/ICSI cycles for infertile women with EMS and adenomyosis.MethodA comprehensive search was conducted across PubMed, EMBASE, MEDLINE, Web of Science, Google Scholar, and Chinese databases to identify studies examining different embryo transfer strategies in IVF/ICSI cycles among patients with EMS and adenomyosis. The outcomes analyzed included rates of implantation, clinical pregnancy, miscarriage, and live birth. Odds ratios (ORs) with 95% confidence intervals (CIs) were calculated using random-effects or fixed-effects models.ResultsIn patients with EMS, the results demonstrated that the FET strategy yielded higher clinical pregnancy (OR: 1.25; 95% CI: 1.11, 1.40), live birth rates (OR: 1.31; 95% CI: 1.15, 1.49), and implantation rates (OR: 1.27; 95% CI: 1.05, 1.54) compared to the fresh ET strategy. The miscarriage rate (OR: 0.89; 95% CI: 0.52, 1.52) and the ectopic pregnancy rate (OR: 0.51; 95% CI: 0.24, 1.07) were comparable between groups. For the group of women with adenomyosis, the IVF/ICSI outcomes were comparable between the FET and fresh ET strategies.ConclusionIn IVF/ICSI, the FET strategy has been associated with more favorable reproductive outcomes compared to the fresh ET strategy in women with EMS. Whereas in women with adenomyosis, pregnancy outcomes were comparable between the FET and fresh ET groups.Systematic Review Registrationhttps://www.crd.york.ac.uk/PROSPERO/view/CRD42024563268, identifier CRD42024563268.